REAKSI PASAR PADA AKSI KORPORASI STOCK SPLIT EMITEN DI BURSA EFEK INDONESIA - Dedeh Sri Sudaryanti; Yuyun Yuniasih; Andri Helmi Munawar (Value : Jurnal Manajemen dan Akuntansi, 2023)
Stock split is one of the corporate activities used to increase stock liquidity. The content of information contained in the company's stock split corporate action still shows that the phenomenon related to the stock split shows inconsistent results. This study aims to obtain empirical evidence by analyzing abnormal returns and stock trading volume before and after the stock split announcement. The research was conducted on companies listed on the Indonesia Stock Exchange in 2021 with a data collection technique using the purposive sampling method and 8 companies were obtained. The data used is secondary data from the official website of the Indonesia Stock Exchange. The research data analysis tool used the Wilcoxon signed rank test with IBM SPSS version 27 through an even study approach with an observation period of 5 days before and 5 days after the stock split event. The results of this study indicate that there is a market reaction as evidenced by a significant difference between abnormal returns and stock trading volume before and after the stock split announcement. Keywords: Stock Split; Abnormal Return